Pengaruh Budaya Birokrasi, Komitmen Organisasi dan Employee Engagement terhadap Kinerja dengan Kepuasan Kerja sebagai Variabel Moderasi - Mulyawan, Moh. Arif; Ariyan, Said; Samudi, Samudi (Jurnal Politikom Indonesiana, 2024)
Employee performance is an important issue in local government administration. Employee performance is the result of an employee's work output in accordance with his ability to realize planned goals. To produce employee performance in a government agency, many factors can influence it, including; bureaucratic culture, organizational commitment, employee engagement and job satisfaction. This study aims to examine the effect of bureaucratic culture, organizational commitment and employee engagement on performance with job satisfaction as a moderating variable. This research took place in the Pamong Praja Police Unit of Lebak Banten Regency. The sample of this study amounted to 75 people, with data collection using observation and questionnaires and documentation. The data analysis used multiple linear regression analysis and Moderated Regression Analysis. The research findings are that bureaucratic culture, organizational commitment and employee engagement have a significant influence on employee performance and job satisfaction can moderate the influence of bureaucratic culture, organizational commitment and employee engagement on employee performance. Keywords: Bureaucratic Culture, Employee Engagement, Employee Performance, Job Satisfaction, Organizational Commitment